Fraud Lelang Jabatan Serta Pengaruhnya Terhadap Persepsi Masyarakat - Kurniawan, Pratomo Cahyo Kurniawan; Rifda Isna Mildana; Rohmad Abidin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to determine how public perception is viewed from the job auction fraud that occurs. Job auctions have often been used to obtain good resources if done correctly. This study uses primary data obtained from distributing questionnaires to the people of Pemalang district using the accidental sampling method. The results of the study indicate that job auction fraud committed by regional heads affects public perception. Regional heads who commit fraud directly receive negative perceptions from the people they lead in their region